Interferon-gamma inhibits the action of B cell stimulatory factor (BSF)-1 on resting B cells. - E M Rabin; J J Mond; J Ohara; W E Paul (1986)
B cell stimulatory factor-1 (BSF-1) stimulates resting B cells to increase in volume and prepares these cells to enter the S phase in response to anti-IgM and other B cell mitogens. Interferon-gamma (IFN-gamma) blocks both the volume enlargement and preparation for DNA synthesis caused by BSF-1, although it has little effect on B cells already stimulated by BSF-1. The capacity of IFN-gamma to inhibit the action of BSF-1 on resting B cells suggests a mutual regulatory interaction between these two T cell-derived products.